iKNOW—Supporting the counseling of women with hereditary risk of breast and ovarian cancer with digital technologies: A randomized controlled trial - Markus A. Feufel; Dorothee Speiser; Stephen Schüürhuis; Konrad Neumann; Marie Keinert; Steffi Stegen; Gudrun Rauwolf; Maren Heibges; Viola Westfal; Laura Besch; Christine Olbrich; Katharina Klein; et al. (Genetics in Medicine Open)
Purpose: We developed the online-based counseling tool iKNOW for women with a pathogenic germline variant in BRCA1/2 to improve risk understanding and quality of life. Methods: With a randomized controlled trial, we investigated the efficacy of iKNOW with regard to risk understanding (primary endpoint), quality of life, risk perception, and anxiety (secondary endpoints). Self-report questionnaires were administered to N = 217 women with a pathogenic variant in BRCA1/2 before counseling (T0), immediately after (T1), 4 weeks after (T2), and 6 months after (T3). Result: Deviations between self-assessed and calculated cancer risks tended to be smaller in the intervention group than in the control group but no longer significantly after adjustment for multiple testing. In the intervention group, the proportion of women with a correct understanding of breast cancer risk at T3 was higher (30.7% vs 14.7%; P = .032). There were no differences in secondary endpoints. Conclusion: iKNOW tends to positively influence the understanding of familial cancer risk. At the same time, it does not negatively influence any of the secondary endpoints. However, converging evidence suggests that iKNOW seems to affect the quality of counseling processes and can thus be used as a paradigm for reinventing the notion of efficient, digital care.